What do social scientists know about the benefits of marriage? : A review of quantitative methodologies - David C. Ribar (Institute for the Study of Labor (IZA), 2004)
This study critically reviews quantitative methods that have been employed and evidence that has been gathered to assess the benefits of marriage and consequences of other family structures. The study begins by describing theoretical models of the determinants of different well-being outcomes and the role of family structure in producing those outcomes. It also discusses models of the determinants of marriage. The study then overviews specific statistical techniques that have been applied in empirical analyses of the effects of marriage, including standard regression, instrumental variables, selection and switching models, matching, non-parametric bounds, fixed effects, and latent factor (correlated random effects) methods. The study then reviews selected studies that have been completed in three domains of well-being outcomes: children's well-being, adults' earnings, and adults' physical health.
Keywords: J1; 330; marriage; well-being; Ehe; Kosten-Nutzen-Analyse; Lebensqualität; Familiensoziologie; Sozialforschung; Welt